The penalty purposes in the Islamic Shariah - dudeen, Basil Ahmad (Journal of Islamic Sciences, 2023)
This research aims at showing the consistency between the Shariah and people’s life besides demonstrating that penalty purposes in Islam are based on both giving people their rights and preventing criminals from committing crimes. The used-methods in this research are the descriptive and the inductive ones with sticking to the scientific research method. The research started with an introduction then two sections and a conclusion. The first section was about the penalty meaning and its types where the second was about the penalty purposes in the Islamic Shariah. The most important outcomes of the research were that there are various penalties in Islam according to how much does the crime affect the individuals and the whole community, and that the principle of Shariah is not to punish people but to polite them.